Rules Britannia: Analysing Britain's regulatory burden - Victoria Hewson (Institute of Economic Affairs (IEA), 2020)
Supporters of free markets often have a general feeling that there is too much regulation or that it is too intrusive, badly formulated, and ineffective. However, proponents of these positions are often lacking in empirical evidence and are susceptible to accusations of either exaggerating the impact of regulation or not caring about the environment, workers, children or consumers. However, supporters of free markets value and recognise the importance of these and believe that market solutions would improve the overall situation. As the UK leaves the EU, it will adopt an independent regulatory policy with the ability to repeal and amend EU rules, and introduce new regulations in fields of EU competence. This freedom will have to be exercised in line with Britain's international commitments and the impact on trade with the EU that will come from diverging at a national level from its regulations. Regulation has been a tool of EU integration. The implications of this driver being removed from UK regulatory policy should not be underestimated. Regulation is a major source of concern for businesses, though the concerns tend to differ between the strategic interests of larger businesses with legal and lobbying firepower and small and new businesses ,for whom the costs of regulation represent barriers to entry and growth. The perception that unelected officials in entrenched positions are enforcing rules contributed to the feelings of dissatisfaction that led British people to vote to leave the EU in 2016. There is a risk now, with EU laws being transposed en masse into UK law and regulators pouring cold water on suggestions of reforms, that the innate stickiness of the regulatory state will assert itself and the opportunity for meaningful change will be lost.
Keywords: K20; L51; L52; L53; O38; H11; E60; K20; L51; L52; L53; O38; H11; E60; 330; Regulation; Regulatory authority; Great Britain; Regulierung; Aufsichtsbehörde; Großbritannien